2020
DOI: 10.1530/ec-20-0089
|View full text |Cite
|
Sign up to set email alerts
|

The role of 68Ga-DOTA derivatives PET-CT in patients with ectopic ACTH syndrome

Abstract: Introduction and aim Ectopic ACTH secretion (EAS) is mostly secondary to thoracic/abdominal neuroendocrine tumours (NETs) or small cell-lung carcinoma (SCLC). We studied the diagnostic accuracy of CT with 68Ga-Dota derivatives (68Ga-SSTR) PET in localizing ACTH-secreting tumor in patients with EAS. Materials and methods 68Ga-SSTR-PET/CT was performed and compared with the nearest enhanced CT in 18 cases (16 primary and 2 recurrent neoplasms). Unspecific, indeterminate and false-positive uptakes were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…18 F-FDG was also found superior to 68 Ga-SSTR imaging in suspected metastasis or in the differentiation between pulmonary infections and ACTHsecreting bronchial tumors in found lung nodules [56,57], while 68 Ga-SSTR appeared superior to 18 F-FDG for de novo ECS tumor detection [51,57]. Conclusions of authors of studies on 68 Ga-SSTR imaging in the tumor detection of ECS were not concordant: while some studies reported high diagnostic accuracy [51,[58][59][60] and found its use helpful in tumor staging and treatment decision making [59][60][61] or even limiting the need for invasive diagnostic procedures [58], others stated that its use should be complementary when conventional imaging is negative or to enhance the positive predictive value of previously found lesions [31,55,[62][63][64]. Dutta et al reported that 68 Ga-DOTA-TOC PET-CT was not useful in the detection of thymic carcinoid, and Varlamov et al suggested that previously reported results on 68 Ga-SSTR imaging for tumor detection in ECS are probably subject to publication bias [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG was also found superior to 68 Ga-SSTR imaging in suspected metastasis or in the differentiation between pulmonary infections and ACTHsecreting bronchial tumors in found lung nodules [56,57], while 68 Ga-SSTR appeared superior to 18 F-FDG for de novo ECS tumor detection [51,57]. Conclusions of authors of studies on 68 Ga-SSTR imaging in the tumor detection of ECS were not concordant: while some studies reported high diagnostic accuracy [51,[58][59][60] and found its use helpful in tumor staging and treatment decision making [59][60][61] or even limiting the need for invasive diagnostic procedures [58], others stated that its use should be complementary when conventional imaging is negative or to enhance the positive predictive value of previously found lesions [31,55,[62][63][64]. Dutta et al reported that 68 Ga-DOTA-TOC PET-CT was not useful in the detection of thymic carcinoid, and Varlamov et al suggested that previously reported results on 68 Ga-SSTR imaging for tumor detection in ECS are probably subject to publication bias [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…While increased uptake could also have occurred because of interval increases in the size of the lesions, there was no evidence of a change in tumor size in these patient cases based on CT imaging. SSTR2 is normally expressed in the pituitary gland ( 33 , 34 ), and increased uptake on 68 Ga-DOTATATE scan is seen in eucortisolemic patients. In the patient with an ACTH-secreting metastatic bronchial NET, there was no physiologic uptake of 68 Ga-labeled somatostatin analog in the pituitary gland at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…68 Ga-DOTATATE imaging of the pituitary showed no uptake at baseline ( Figure 4E ). Normally, the pituitary gland expresses SSTR2, and physiologically increased uptake is seen in eucortisolemic patients’ DOTATATE scans ( 33 , 34 ). During relacorilant treatment, however, the pituitary uptake was restored ( Figure 4E ).…”
Section: Clinical Observationsmentioning
confidence: 99%
“…Напротив, в исследовании Ceccato F. et al [32,39]. Например, в работе Varlamov Е. et al [38] 7 из 9 карциноидных опухолей высокой степени злокачественности хорошо выявлялись при проведении ПЭТ/КТ с соматостатином, меченным галлием-68.…”
Section: таблицаunclassified